Projection of the Spatially Explicit Land Use/Cover Changes in China, 2010–2100 - Yongwei Yuan; Tao Zhao; Weimin Wang; Shaohui Chen; Feng Wu (Advances in Meteorology)
Land use/cover change (LUCC) is an important part of the global environmental change. This study predicted the future structure of land use/cover on the basis of the Global Change Assessment Model (GCAM) and an econometric model with the socioeconomic factors as the driving forces. The future spatial pattern of land use/cover in China was simulated with the Dynamics of Land System (DLS) under the Business as Usual scenario, Rapid Economic Growth scenario and Cooperate Environmental Sustainability scenario. The simulation results showed that the land use/land cover in China will change continually due to the human activities and climate change, and the spatial pattern of land use/cover will also change as time goes by. Besides, the spatial pattern of land cover in China under the three scenarios is consistent on the whole, but with some regional differences. Built-up area will increase rapidly under the three scenarios, while most land cover types will show a decreasing trend to different degrees under different scenarios. The simulation results can provide an underlying land surface data and reference to the methodology research on the prediction of LUCC.